Narrativa crítico-reflexiva sobre o curso de medicina: sobre as dificuldades, prazeres e experiências no trajeto de apfrender a aprender - Ferreira Júnior, Júlio César (Universidade Federal de São Carlos, 2024)
In this work I seek to briefly express reflections on the medical course cycles at the Federal University of São Carlos, their difficulties and transformative experiences. I intend to address how the different undergraduate scenarios were important for my learning process, that is, how I learned to learn.
Critical-reflective narrative about the medicine course: about the difficulties,pleasure and experiences on the journey from learning to learn
Keywords: Educação médica; Narrativa; Metodologias ativas; Reflexão; Medicina; Medical education; Narrative; Active methodologies; Reflection; Medicine; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM